(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
These days, cell phones are becoming an essential component of people’s daily lives. According to recentsurveys, themajorityofthecorporateandtele-communication sectorswillintegrateMobileCloud Computing (MCC) in order to efficiently satisfy their business needs. Mobile Cloud Computing (MCC) integrates cloud computing with mobile devices, offering enhanced computational power and storage capabilities. This paper provides a comprehensive analysis of real-time data processing in MCC environments, exploring challenges, opportunities, and future directions. We discuss computational offloading, network latency, security concerns, and resource management strategies to optimize performance. Since 2009, the term "mobile cloud computing" (MCC), which blends cloud computing with mobile computing, has gained popularity and become a hot topic in the IT community. Since MCC is still in its infancy, being able to identify the path of future research requires having a solid understanding of the technology. In order to achieve the latter goal, this paper provides an overview of the history and tenets of MCC, as well as its features, current research, and potential directions for future study. Following a brief overview of MCC’s history—from mobile computing to cloud computing—a review of its features and current research is given. The infrastructure and characteristics of mobile cloud computing are then examined. The remainder of the paper examines the difficulties associated with mobile cloud computing, provides an overview of various relevant research efforts, and identifies possible avenues for further investigation.